2018
DOI: 10.15439/2018f95
|View full text |Cite
|
Sign up to set email alerts
|

Improved Analogy-based Effort Estimation with Incomplete Mixed Data

Abstract: Estimation by analogy (EBA) is one of the most attractive software effort development estimation techniques. However, one of the critical issues when using EBA is the occurrence of missing data (MD) in the historical data sets. The absence of values of several relevant software attributes is a frequent phenomenon that may cause inaccurate EBA estimations. The MD can be numerical and/or categorical. This paper evaluates four MD techniques (toleration, deletion, k-nearest neighbors (KNN) imputation and support v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The results shown that SVR imputation is less sensitive regarding MD percentage compared to KNN imputation. The results confirmed that for both SVR imputation and KNN imputation had worse performance under MNAR mechanism compared to both MAR and MCAR [43]. Numerical and categorical MD toleration, deletion, KNNI, SVR imputationMAR MCAR MNARFindingThe results confirmed that imputation techniques achieved better accuracy improvements compared to toleration and deletion.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…The results shown that SVR imputation is less sensitive regarding MD percentage compared to KNN imputation. The results confirmed that for both SVR imputation and KNN imputation had worse performance under MNAR mechanism compared to both MAR and MCAR [43]. Numerical and categorical MD toleration, deletion, KNNI, SVR imputationMAR MCAR MNARFindingThe results confirmed that imputation techniques achieved better accuracy improvements compared to toleration and deletion.…”
supporting
confidence: 71%
“…Idri, Abnane et al[42] proposed SVR (Support Vector Regression) imputation, empirical results indicated that SVRI outperformed KNNI under different missing ratio and MD mechanisms for ABE model. Abnane and Idri[43] investigated mixed (Numerical and categorical) MD imputation techniques for ABE model, imputation techniques achieved better accuracy results, there is no significant difference between SVR and KNNI for mixed MD imputation. Muhammad Arif Shah[44] proposed Median Imputation of the Nearest Neighbor (MINN) for ABE mode , the investigation of the proposed model under Desharnais dataset outperformed both MI and KNN under MNAR mechanism.Abnane, Hosni et al[45] optimize parameters of KNN imputation using grid search, the optimize KNN imputation improved ABE significantly compared with regular KNN imputation.…”
mentioning
confidence: 99%
“…KNN imputation (KNNI) is widely used to deal with the MD issue due to its simplicity, popularity, and usefulness. 2,5,6,11 KNNI, which is based on case-based reasoning, computes the similarity between an incomplete project and complete projects by using a distance function and then uses the most similar projects to impute the MD.…”
Section: Problem Statementmentioning
confidence: 99%
“…Therefore, feature subset selection techniques should be applied to find the optimal set of features . Another important limitation of ASEE techniques is their inability to handle missing values …”
Section: Introductionmentioning
confidence: 99%